2005
DOI: 10.1186/1746-1340-13-23
|View full text |Cite
|
Sign up to set email alerts
|

Influence of static lumbar flexion on the trunk muscles' response to sudden arm movements

Abstract: BackgroundViscoelastic creep of lumbar ligaments (prolonged forward bend) has been shown to negatively influence the spine's muscular reflexive behaviour and spinal stability. No studies to date have investigated the influence of spinall viscoelastic creep on the feedforward response of the trunk muscles to sudden arm raises.MethodsSurface myoelectric activity was collected from the transversus abdominis/internal oblique, the lower erector spinae and the deltoid muscle during sudden ballistic arm raising befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Numerous studies have been conducted on the use of this tool to measure muscle activity by EMG [6,[11][12][13]. According to Lehman et al, who recorded muscle activity using EMG, the use of a Swiss ball in the front plank increased the activity of the rectus abdominis and external oblique muscles; however, it did not affect the internal oblique and erector spinae muscles [18]. The current research findings are in line with their results regarding the internal oblique muscle.…”
Section: Discussionsupporting
confidence: 86%
“…Numerous studies have been conducted on the use of this tool to measure muscle activity by EMG [6,[11][12][13]. According to Lehman et al, who recorded muscle activity using EMG, the use of a Swiss ball in the front plank increased the activity of the rectus abdominis and external oblique muscles; however, it did not affect the internal oblique and erector spinae muscles [18]. The current research findings are in line with their results regarding the internal oblique muscle.…”
Section: Discussionsupporting
confidence: 86%
“…These findings are supported by the results of other experiments. Many authors noted that the mechanism of motor control of the deep abdominal muscles is based on random muscle activation in both normal and painful conditions [32][33][34]. This might suggest that 'plasticity' constitutes a characteristic feature of the pattern of deep abdominal muscle activation, and it often depends on the character of the given motor task (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effects of active or passive prolonged deep flexions of the trunk on low back muscle activity are not well understood. Indeed, no change has been observed in the timing of muscle activation onset for the lower erector spinae muscles following a static passive lumbar flexion period of 10 [ 19 ] or 15 minutes [ 14 ], whereas onset latency of the same muscles increased after one hour of static passive lumbar flexion [ 20 ]. Olson et al showed that no difference exists regarding onset latency of the lower erector spinae muscles following either active or passive trunk flexion-extension repetitions [ 21 ].…”
Section: Introductionmentioning
confidence: 99%